Expansion of the phenotypic and genotypic spectrum for PRKAR1B-related Marbach-Schaaf neurodevelopmental syndrome: a case series - Burkart, Sebastian; Guzeloglu, Tarik; Soares, Ana R.; Valenzuela, Irene; Tizzano, Eduardo F.; Gómez-Andres, David; Pasquier, Laurent; Legendre, Marine; Berges, Camille; Thevenon, Julien; Gauthier, Marjolaine; Heid, Caleb; et al. (Clinical genetics, 2025)
Marbach-Schaaf neurodevelopmental syndrome (MASNS) is an ultra-rare, monogenic disease caused by pathogenic variation in PRKAR1B, which codes for the R1β regulatory subunit of protein kinase A (PKA), a key effector of cAMP signaling within the nervous system. This work provides a comprehensive clinical description of 12 subjects with pathogenic PRKAR1B variants, including two individuals with a heterozygous deletion including PRKAR1B, supporting haploinsufficiency as a possible mechanism of disease. Phenotypic information was obtained by interview, using a systematic multi-dimensional questionnaire. Besides expanding the evidence for established MASNS phenotypes like developmental delay, ID, ASD, pain insensitivity, as well as mild dysmorphisms, we broaden the clinical spectrum through the description of new and underreported findings, in particular increased body weight. In addition, the presence of genomic deletions suggests dosage sensitivity of PRKAR1B, demonstrating that both sequence and copy number variants should be considered in diagnostic testing. This work gives valuable insight into the pathophysiology of MASNS and sets a framework upon which to design future mechanistic studies of PKA signaling in brain development.